PERFORMA EFISIENSI TEKNIS UNIT USAHA SYARIAH BANK PEMBANGUNAN DAERAH DI PULAU SUMATRA - eko fajar cahyono (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
Economic development in the region is important, therefore the role of the Regional Development Bank (BPD) in advancing the regional economy becomes crucial. The good performance of BPD is expected to sustain the region's economic turnaround. The economic development of Islam in the area responded by way of BPD establish Islamic Business Unit. One of the main indicators of performance is the efficiency that is how the BPD manage their own resources to the maximum. These studies aim to investigate the extent to which the efficiency of Islamic business units Regional Development Banks Island Sumatera. The method used is the Data Envelope Analysis. Data are obtained on the financial statements issued each unit of Islamic business units. Results of research addressing, in general, the majority of Islamic business units of regional development banks on the island of Sumatra has achieved good efficiency except for the BPD Bangka Belitung.